Standing ground : Yurok Indian spirituality, 1850-1990 - Buckley, Thomas C. T. (University of California Press, 2002)
This account of spiritual training and practice within an American Indian social network emphasizes narrative over analysis. Thomas Buckley's foregrounding of Yurok narratives creates one major level of dialogue in an ethnography that features dialogue as its central theoretical trope. Buckley places himself in conversation with contemporary Yurok friends and elders, with written texts, and with twentieth-century anthropology as well.